2022
DOI: 10.3389/fpsyg.2022.981500
|View full text |Cite
|
Sign up to set email alerts
|

Why emotions need to labor—Influencing factors and dilemmas in the emotional labor of Chinese English teachers teaching online

Abstract: During the COVID-19, online teaching has become a popular way of teaching in the world. Previous research on English language teachers’ emotional labor has not focused on the changes brought about by online teaching. Unlike the traditional physical teaching space, the emotional labor of English teachers teaching online changes with the daily use of online technological conditions. Therefore, this paper aims to investigate the factors influencing teachers’ emotional labor in online teaching and the emotional la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…For example, based on qualitative data including multiple semi-structured interviews, class observations, teacher reflective notes, student feedback, and institutional documents over 18 months, Ding et al (2022) explored the dynamic and diachronic emotion labor of two veteran English lecturers in Chinese universities and found that the long-term surface acting of depressing negative emotions is positively related to job burnout and negatively correlated to teachers’ efficacy. Wang and Song (2022) adopted a qualitative method of interviews and online classroom observations conducted with 20 Chinese English teachers to explore the changes on EFL teachers’ emotional labor brought about by online teaching, and found that a variety of factors, such as the degree of adaptation to online teaching technology and the invisibility of the online teaching space, contribute to EFL teachers’ emotional labor that can cause job burnout and professional identity dilemmas. Guo (2022) adopted narrative research to narrate the dynamic formation process of a primary school English teacher’s job burnout, through observation, interviews and information analysis of the interviewee’s Wechat, Weibo and Douyin contents.…”
Section: Resultsmentioning
confidence: 99%
“…For example, based on qualitative data including multiple semi-structured interviews, class observations, teacher reflective notes, student feedback, and institutional documents over 18 months, Ding et al (2022) explored the dynamic and diachronic emotion labor of two veteran English lecturers in Chinese universities and found that the long-term surface acting of depressing negative emotions is positively related to job burnout and negatively correlated to teachers’ efficacy. Wang and Song (2022) adopted a qualitative method of interviews and online classroom observations conducted with 20 Chinese English teachers to explore the changes on EFL teachers’ emotional labor brought about by online teaching, and found that a variety of factors, such as the degree of adaptation to online teaching technology and the invisibility of the online teaching space, contribute to EFL teachers’ emotional labor that can cause job burnout and professional identity dilemmas. Guo (2022) adopted narrative research to narrate the dynamic formation process of a primary school English teacher’s job burnout, through observation, interviews and information analysis of the interviewee’s Wechat, Weibo and Douyin contents.…”
Section: Resultsmentioning
confidence: 99%
“…The job demands in teaching refer to the rules and expectations of organizations or managers regarding the display of emotions by employees [40]. Continuous reforms in higher education have led to higher demands on university teachers, not only in terms of increased class hours but also in terms of using high levels of emotions to enhance the quality of teaching, which has been confirmed by many studies [6,13]. Teachers in higher education are subjected to various demands in their work that subsequently affect their emotions when interacting with students [41].…”
Section: Emotional Job Demands Of Teaching and University Teachers' E...mentioning
confidence: 93%
“…Despite the growing recognition of teachers' emotional labor in recent years, research focusing on teaching-related emotional labor still needs to be completed. Previous studies have predominantly focused on analyzing the dimensions and magnitude of emotional labor [8,9], as well as antecedent variables such as work pressure [10], and outcome variables such as burnout [11,12], job satisfaction [13,14], and well-being [15]. However, these studies have mainly focused on individual teachers, leaving little knowledge about the relationship between teachers' emotional labor and teaching efficacy, a key performance indicator.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are some studies examining online teaching emotions indirectly. Wang and Song (2022) took interviews with a group of English teachers in China and found that their online teaching emotions were influenced by three main factors: the degree of adaptation to online teaching technology, the invisibility of the online teaching space, and the peripheral environment of the space in which the teachers were located. In addition, this study observed the online classrooms of the interviewees and found that the first two influences are at a priority level for Chinese English teachers, while whether the third factor can bring positive or negative emotions is often influenced by the nature of the emotions brought by the first two factors.…”
Section: Teachers' Emotional Experiences In O Ine and Online Teaching...mentioning
confidence: 99%
“…It is constructed through their interactions with students, colleagues, administrators, and other parties in their respective pedagogical, institutional, and sociohistorical contexts (Ding et al, 2022). Previous studies have sought to investigate teacher emotion in the context of both offline teaching (e.g., Gkonou and Miller, 2021;Nazari et al, 2023) and online teaching (e.g., Gu et al, 2022;Liu et al, 2022Liu et al, , 2023Wang and Song, 2022). Researchers found that although teachers in the offline teaching context shared some unpleasant emotional experiences (such as frustrations and anxiety), their dominant emotions were more positive than negative (Cross and Hong, 2012;Richards, 2022;Goetze, 2023).…”
Section: Introductionmentioning
confidence: 99%